Mass movements of differing magnitude and frequency in a developing high-mountain area of the Moxi basin, Hengduan Mts, China – A hazard assessment. (October 2017) - Malik, Ireneusz; Wistuba, Małgorzata; Tie, Yongbo; Owczarek, Piotr; Woskowicz-Ślęzak, Beata; Łuszczyńska, Katarzyna
Abstract: Assessment and management of mass-movement hazard in developing mountain areas is a significant human problem. It can only be resolved through identifying the background behind the processes, including their magnitude and frequency. However, catchment monitoring is rare and historical records are often fragmentary or absent. In such cases dendrochronology can be one of the most precise methods for dating past mass-movement events. Our study is intended to provide a tree-ring based discussion of hazards caused by mass movements in a developing high-mountain area. The goal is to estimate the frequencies and magnitudes of mass movements of differing origin and scale: large and smaller debris flows, and rockfalls, typically endangering the population of the Moxi basin. On the terraces and slopes of the Xiaohezi gully the ages of 30 spruce trees were determined indicating the date of the last large debris flow moulding terrace levels. On the Daozhao debris cone we determined the dates of the events of smaller debris flows wounding the stems of 43 alder trees. On the Nimatuo Study Site the dates of rockfalls injuring the stems of a sample of 15 alder trees were determined. The results allowed the recurrence intervals of the mass movements observed in each study site to be calculated. During the last 55 years large debris flows originating in the vast, high-elevation and glaciated Xiaohezi catchment occurred every 18 years. During the last 20 years smaller debris flows fed from the mid-sized and medium elevation Daozhao catchment occurred every 7 years. Rockfalls, with a very small and steep source area (Nimatuo Site) occurred every 2.85 years. In general, the level of mass-movement activity in the study area is high. Based on the results from three study sites representing typical mass-movement hazards, the densely inhabited main valley of the Moxi basin is affected by 40 large debris flows, hundreds of smaller debris flows and thousands of single rockfalls per century. The hazard affects as much as 27.07% of developed area of the Moxi basin. However, thanks to sustainable land use, the majority is affected by manageable, high frequency, but middle-to low-magnitude phenomena. Highlights: Management of mass-movement hazard is a significant problem in high mountain areas. Tree-rings were used to estimate recurrence intervals of debris flows and rockfalls. Mass-movement activity is high and affects 27.07% of the developed part of the basin. Most of the populated area is affected by low-magnitude but frequent debris flows. Tree-ring reconstructions are a useful tool in assessment of mass-movement hazards.